الزمن التراجيدي في رواية دمية النار لبشير مفتي -أنموذجا - كحيل, سهيلة; برادعي, كريمة; سوالمي, وصال (جامعة الوادي - University of Eloued, 2023)
تتناول المذكرة موضوعا اجتماعيا، سياسيا يخصّ الجزائر فترة العشرية السوداء؛ تسعينيات القرن العشرين، حيث كان صاحب رواية "دمية النّار" الروائي الجزائري بشير مفتي؛ وهي شخصيةٌ ذات مرجعية تاريخية، سياسية، واجتماعية ،ومن كتاباته نرى تأثره بالوضع في الجزائر على مدار ثلاثة عقود. Summary: The memorandum deals with a social and political issue pertaining to Algeria during the black decade. The nineties of the twentieth century, when the author of the novel "The Doll of Fire" was the Algerian novelist Bashir Mufti; She is a figure with historical, political, and social reference, and from his writings we see his influence on the situation in Algeria over the course of three decades.
Keywords: دمية النّار- الوضع السياسي والاجتماعي- رضا شاوش- العشرية السّوداء.; The Fire Puppet - The Political and Social Situation - Reda Shawish - The Black Decade.